Vocal music for children in the opus of Miloje Milojevic - Tasić Nataša D. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2012)
Miloje Milojevic (1884-1946) is one of the most prominent Serbian composers of the first half of the twentieth century. Years of education in European centers of music vanguard strongly influenced on his work. Even though he is mostly known as a composer with strong affinity for modernity and modern tendencies, Miloje Milojevic contributed a lot to the development of music pedagogy. His books and instructions for music teachers, as well as his choral music for children choirs were among most important literature of its kind in first half of the twentieth century in Serbia. Milojevic's works for young singers were written on lyrics of Serbian romantic poets such are Zmaj, Santic, and Grcic-Milenko. Major characteristics of these compositions are clearly defined music accentuation of texts; clear form and metrics; and pure melodic and harmonic lines. All of these characteristics of Milojevic's choral works for children recommend them as adequate for singing with preschoolers and school children.